Integrating engineered nanomaterials with extracellular vesicles: advancing targeted drug delivery and biomedical applications - Jiang, Hai; Kumarasamy, Ranil Vikraman; Pei, JinJin; Raju, Kamaraj; Kanniappan, Gopalakrishnan Velliyur; Palanisamy, Chella Perumal; Mironescu, Ion Dan (Frontiers in Nanotechnology, 2025)
Extracellular vesicles (EVs), natural membrane-bound structures released by cells, offer a promising platform for precise and targeted delivery of therapeutic payloads, including drugs and nanoparticles. This comprehensive review explores the integration of engineered nanomaterials with EVs to advance drug delivery systems. It covers various aspects of this integration, including techniques for synthesizing, loading, characterizing, and applying nanomaterials within EVs. Methodologies for integrating diverse nanocarriers like nanoparticles, liposomes, and quantum dots into EVs are discussed, along with characterization methods such as electron microscopy and light scattering. Attention is also given to considerations of biological compatibility, safety assessments, and strategies for surface modification to enhance targeting precision. Highlighting various applications, including targeted drug delivery, cancer therapy, and vaccine development, the review underscores the potential of EV-nanomaterial hybrids to leverage EVs’ innate targeting capabilities and the versatility of nanomaterials. However, it also addresses challenges such as scalability, standardization, and safety that must be overcome to facilitate the clinical translation of these promising biomedical solutions.